Starling: Lightweight Concurrency Verification with Views - Windsor, Matt; Dodds, Mike; Simner, Ben; Parkinson, Matthew (Computer Aided Verification 2017, 2017)
Modern program logics have made it feasible to verify the most complex concurrent algorithms. However, many such logics are complex, and most lack automated tool support. We propose Starling, a new lightweight logic and automated tool for concurrency verification. Starling takes a proof outline written in an abstracted Hoare-logic style, and converts it into proof terms that can be discharged by a sequential solver. Starling’s approach is generic in its structure, making it easy to target different solvers. In this paper we verify shared-variable algorithms using the Z3 SMT solver, and heap-based algorithms using the GRASShopper solver. We have applied our approach to a range of concurrent algorithms, including Rust’s atomic reference counter, the Linux ticketed lock, the CLH queue-lock, and a fine-grained list algorithm.